Application-based Elementary Schools Interactive Education Platform Analysis and Design - Felix, Antonius; Bernanda, Devi Yurisca; Kembau, Agung Stefanus; Effendy, Filberth; Nathaniel, Regan (Pandawan Sejahtera Indonesia, 2025)
The rapid digital transformation fueled by widespread Internet use has significantly impacted education. As of April 2023, there are over 5.18 billion Internet users worldwide, necessitating innovative educational solutions. This study analyzes and designs an interactive educational platform tailored for elementary students aged 7-12, employing technologies such as Artificial Intelligence (AI) and Augmented Reality (AR) to enhance learning. The platform emphasizes user-friendly interfaces and engaging content to boost children's motivation and participation. Despite the potential of digital educational tools, challenges such as unequal access to technology, screen addiction, and the need for improved digital literacy persist. This study addresses these issues by proposing a platform that provides equitable access and delivers high-quality, safe, and educationally rich content. The design process involved a literature review, iterative user interface development, and collaboration with educational professionals to meet the specific needs of young users. By integrating interactive multimedia and contemporary interface technologies, the platform offers a personalized and differentiated learning experience beyond traditional methods. The study highlights the significant potential of digital learning tools in improving education quality for children while addressing access and security challenges. Ultimately, this research aims to develop effective educational technologies that support sustainable education for young learners in the digital age.